The acoustics of ancient catacombs in Southern Italy. Issue 4 (December 2021) - Ciaburro, Giuseppe; Berardi, Umberto; Iannace, Gino; Trematerra, Amelia; Puyana-Romero, Virginia
The catacombs, burial sites for early Christians, were constructed during the Roman Empire until the Christian religion was recognized in 313 AD. The catacombs were cementeries, which were organized according to precise rules and were dug into the ground on several levels, to occupy as little space as possible. The catacombs became places of worship as martyrs were buried in them. The catacombs were then abandoned with the barbarian invasions and the consequent construction of churches inside cities. The catacombs were rediscovered during the Renaissance period and became a place of renewed worship. In the present work, the acoustic characteristics of the catacombs of San Callisto in Rome, San Gennaro in Naples, and Vigna Cassia in Syracuse are discussed. The three selected catacombs differ by type of excavation and geometry. In particular, the catacombs of San Callisto are made of narrow corridors and small rooms; the catacombs of San Gennaro consist of large rooms with niches; the catacombs of Vigna Cassia are partly excavated in the tuff and partially occupy a disused aqueduct. The acoustic measurements were performed using an impulsive sound source. The description of the acoustic characteristics focuses on the reverberation time and the Speech Transmission Index. The results show that the reverberation time was always shorter than 1 second, confirming the reduced reverberation of these environments. Finally, the speech listening characteristics are particularly good, ensuring the suitable conditions for the prayer in these spaces.